MANAJEMEN PEMANFAATAN DANA BANTUAN OPERASIONAL SEKOLAH (BOS) UNTUK MENINGKATKAN MUTU PENDIDIKAN SEKOLAH DASAR SWASTA DI SD ISLAM CENDEKIA MAKASSAR - Nur Alfiaty Risyidah; Rosmiati; Abdul Wahab; Nurlaelah; Hasibuddin Mahmud; Abd. Rauf Assagaf (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the management of School Operational Assistance Fund (BOS) utilization in improving educational quality at SD Islam Cendekia Makassar, a private elementary school that began receiving BOS funds in 2024. The research focuses on three main aspects: (1) planning of BOS fund utilization; (2) implementation of BOS fund utilization; and (3) monitoring and evaluation of BOS fund utilization. This study employs a qualitative approach with a phenomenological method. Data were collected through in-depth interviews, field observations, and documentation. The key informants included the school principal, the BOS treasurer, and teachers. Data analysis was conducted using the interactive analysis model of Miles, Huberman, and Saldana, comprising data reduction, data display, and conclusion drawing with verification. The findings reveal that: (1) Planning was carried out systematically and participatively through data-driven RKAS formulation involving the principal, treasurer, teachers, and foundation manager, with priorities on textbook procurement, assessments, facility maintenance, and library development; (2) Implementation adhered to BOS technical guidelines and positively impacted the availability of learning materials, improved facility conditions, and a more conducive learning environment; (3) Monitoring was conducted through a multilayered mechanism involving both internal and external oversight with orderly reporting via the ARKAS system, although formal periodic evaluation has not yet been systematically implemented. The study concludes that BOS fund management at SD Islam Cendekia Makassar has positively contributed to improving educational quality, though further strengthening of evaluation mechanisms and management capacity remains necessary.